A gaming app developed for vestibular rehabilitation improves the accuracy of performance and engagement with exercises - D’Silva, Linda J.; Phongsavath, Tarah; Partington, Kelly; Pickle, Nathan T.; Marschner, Katherine; Zehnbauer, Timothy P.; Rossi, Michael; Skop, Karen; Roos, Paulien E. (Frontiers in Medicine, 2023)
Vestibular hypofunction is associated with dizziness, imbalance, and blurred vision with head movement. Vestibular rehabilitation is the gold standard recommendation to decrease symptoms and improve postural stability. The Clinical Practice Guidelines for vestibular hypofunction suggest home exercises 3 to 5 times daily, but patient adherence is a problem, with compliance rates often below 50%. An app was developed to increase engagement with home exercises by providing exercises as games. This study compared the accuracy of exercise performance in a one-time session using the app versus no app and gathered participant feedback on using the app for vestibular-ocular (VOR) and balance exercises. The app was tested with 40 adults (20 females), mean age of 67±5.7 years, with symptomatic unilateral or bilateral vestibular hypofunction. Participants completed VOR exercises in pitch and yaw planes, weight-shift, and single-leg balance exercises using an inertial motion unit to move the character on the tablet screen. Participants were randomly assigned to begin the exercises with or without the app. Results show that during VOR exercises, participants achieved the prescribed frequency of head motion for the yaw plane (p≤0.001) and reduced variability of head movement frequency in both yaw (p≤0.001) and pitch plane (p≤0.001) in the app compared to the no app condition. During weight-shifting exercises, a larger range of body motion was noted in the anteroposterior and mediolateral directions in the app compared to the no-app condition (p<0.05). During single-leg balance exercises, pelvic motion was lower in the app versus no app condition (p=0.02). Participants modified their exercise performance and corrected their mistakes to a larger extent when they used the app during the VOR exercises. Participants agreed that they felt motivated while playing the games (97%) and felt motivated by the trophies (92%). They agreed that the app would help them perform the exercises at home (95%), improve their rehab performance (95%), and that it was fun to do the exercises using the app (93%). The results of this study show that technology that is interactive and provides feedback can be used to increase accuracy and engagement with exercises.